2016
DOI: 10.3390/en9121021
|View full text |Cite
|
Sign up to set email alerts
|

Gas Hydrate Growth Kinetics: A Parametric Study

Abstract: Gas hydrate growth kinetics was studied at a pressure of 90 bars to investigate the effect of temperature, initial water content, stirring rate, and reactor size in stirred semi-batch autoclave reactors. The mixing energy during hydrate growth was estimated by logging the power consumed. The theoretical model by Garcia-Ochoa and Gomez for estimation of the mass transfer parameters in stirred tanks has been used to evaluate the dispersion parameters of the system. The mean bubble size, impeller power input per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
2
5
0
Order By: Relevance
“…This result indicates that hydrate crystals nucleate more easily at lower temperature conditions due to the stronger driving force. Moreover, since the hydrate formation is an exothermic process, at a lower temperature, the heat released during hydrate formation can be removed more quickly at a lower temperature. ,, In the work of Meindinyo et al, study of hydrate formation in pure water, hydrate nucleation or growth rate decreased in a roughly linear and inversely proportional relationship with increasing temperature, which is consistent with the experimental results of this work which spanned a limited range of temperatures. Thus, temperature appears to exert the same effect on hydrate induction times in both pure water and emulsions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This result indicates that hydrate crystals nucleate more easily at lower temperature conditions due to the stronger driving force. Moreover, since the hydrate formation is an exothermic process, at a lower temperature, the heat released during hydrate formation can be removed more quickly at a lower temperature. ,, In the work of Meindinyo et al, study of hydrate formation in pure water, hydrate nucleation or growth rate decreased in a roughly linear and inversely proportional relationship with increasing temperature, which is consistent with the experimental results of this work which spanned a limited range of temperatures. Thus, temperature appears to exert the same effect on hydrate induction times in both pure water and emulsions.…”
Section: Resultssupporting
confidence: 88%
“…Both induction time and nucleation rate will be used here to analyze the effects of water cut. The relationship between induction time, T induction , and nucleation rate, α, is given by the relationship In theory, the hydrate nucleation probability should be proportional to quantity of water . Consequently, one might expect the induction time to be inversely proportional to the water cut (see Case 2 discussion below), as shown by the blue dotted line in Figure that uses the pure water value as a reference point.…”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamic promoters, such as tetrahydrofuran (THF), for example, enable gas hydrate formation at higher temperatures and lower pressures, as they are capable of forming hydrates on their own while stabilizing gas hydrates of other species. , Kinetic promoters, mainly surfactants, such as sodium dodecyl sulfate (SDS), accelerate gas hydrate formation. , For example, Zhong and Rogers discovered that, at SDS concentrations above the CMC, gas hydrate formation rates in quiescent systems are significantly higher than those in pure water . Recently, growing interest in amino acids has been recognized as well in this context. , Another approach to enhance hydrate formation is to take apparatus-based technical measures, for example, by using stirred, , spray, , bubble column, , or packed-bed , reactor designs, and this work focuses on the last approach.…”
Section: Introductionmentioning
confidence: 99%
“…30 Recently, growing interest in amino acids has been recognized as well in this context. 31,32 Another approach to enhance hydrate formation is to take apparatusbased technical measures, for example, by using stirred, 33,34 spray, 35,36 bubble column, 37,38 or packed-bed 39,40 reactor designs, and this work focuses on the last approach.…”
Section: Introductionmentioning
confidence: 99%
“…Stirring frequency was set to 900 rpm, leading to turbulent conditions at Re ≈ 10 571. According to our experience, this is the optimal value for this system, as several studies showed that the effect of stirring on hydrate formation is apparatus‐dependent , . The experimental setup is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%